Controlling of Five Axis Manipulator with Turkish Voice Commands Using Microcontrollers - AK, AYÇA; TOPUZ, VEDAT (My University, 2018)
The interaction between human beings and machines has been increasing in conjunction with the development of computer technology.Controlling a system with voice-based commands is one of the most popular applications in this area. In this study, the main goal is to builda system, which is able to control a robotic arm comprised of five controllable axes with certain voice commands.The robotic arm controlling process starts with the matching of sounds taken from the user. Then sounds processed in voice recognitioncard. After the command recognized by voice recognition card, then index number is sent to a microcontroller. Consequently, this operationprovides a communication between voice recognition module and servo motor drive card. Finally, the microcontroller calculates therequired angles by using the data provided by the previous process and sends this data to the servo motor drive card in order to realize therobotic arm action.

Bilgisayar teknolojisi gelişimiyle birlikte, insanlar ile makineler arasındaki etkileşim artmaktadır. Ses tabanlı komutlarla bir sistemi kontrol etmek bu alandaki en popüler uygulamalardan biridir. Bu çalışmada ana hedef, belirli sesli komutlarla beş kontrol edilebilir eksenden oluşan robot kolunu kontrol edebilen bir sistem oluşturmaktır. Robot kolunu kontrol etme işlemi, kullanıcıdan alınan seslerin ve ses tanıma kartında işlenmiş ve ses tanıma kartı tarafından tanımlanan seslerin eşleştirilmesi ile başlar. Ardından pozitif bir eşleme varsa, sistem tarafından ses tanıma modülü ve servo motor sürücü kartı arasında bir iletişim sağlayan bir mikrodenetleyiciye veri gönderilir. Son olarak, mikrodenetleyici, önceki işlem tarafından sağlanan verileri kullanarak gerekli açıları hesaplar ve robotik kol hareketini gerçekleştirmek için bu verileri servo motor sürücü kartına gönderir.
Mikrodenetleyicileri Kullanarak Türkçe Sesli Komutlarla Beş Eksenli Manipülatör Kontrolü
Keywords: Kimya, Analitik; Kimya, Uygulamalı; Kimya, İnorganik ve Nükleer; Kimya, Tıbbi; Kimya, Organik; Çevre Bilimleri; Matematik; Fizik, Matematik; Mühendislik, Kimya; Mühendislik, Elektrik ve Elektronik; Endüstri Mühendisliği; Mühendislik, Makine; Malzeme Bilimleri, Biyomalzemeler